Marketing Communication Strategy of Clam Meatballs through Packaging and Labeling Training during the Covid-19 Pandemic - Sri Tjondro Winarno; Dwi Wahyuningtyas; Didiek Tranggono (Nusantara Science and Technology Proceedings, 2021)
Marketing communication strategies through labeling and packaging of processed food products are very important in improving the quality of the product results. Therefore, it needs special attention from various parties, from the government, private sector, and universities. Coastal communities are often associated with poor people who have complex problems. Besides being economically poor, they are socially marginalized, and forgotten in function and dignity. Furthermore, the education level of coastal communities is mostly still low. It is an ironic thing as education is essential because, with empowerment, the community will increase the capacity of individuals and groups. One of the coastal communities in Sidoarjo District is the fishing community in Bluru Kidul Village, Sidoarjo Sub-district, Sidoarjo District. One of the solutions to increase the income of fishermen's families is the participation of women in the fishing industry is seeking additional income. Therefore, clam meatballs in this village have the potentials to be developed. Still, due to limited human resources capabilities, especially knowledge in creating and developing home industry and marketing businesses, the clam meatballs home industry business in Buru Kidul Village, Sidoarjo Sub-district, Sidoarjo District cannot grow well, especially during this COVID-19 pandemic.